Research on 5G+MEC Industrial Internet Technology Testing Platform. (November 2020) - Dazhi, Jing; Xiaoping, Lu; Weijie, Zhang; Ming, Sun; Yubao, Huang; Rui, Zhu
Abstract: The 5G+MEC Industrial Internet technology test platform is committed to the application of 5G technology in industrial scenarios. The test platform is supported by 5G+MEC as the technical architecture, and is integrated with machine vision, AR, AGV and other applications; The test platform adopts a modular design. Starting from the test scenarios of the manufacturing process such as interaction, customization, and production, some technologies are transformed into mature solutions through testing, which shortens the application cycle of new technologies and promotes the development of the Industry. Internet.